Inkonsistensi Pemikiran Nashir al-Din al-Bani: Analisis Kritis atas Kitab al-Ajwibah al-Nafi’ah ‘an Mas’alah Masjid al-Jami’ah - Arif Nuh Safri (Faculty of Ushuludin Institute of Al-Qur’an Science (IIQ) An Nur Yogyakarta Indonesia, 2021)
The science of the criticism of the Prophet's hadith is likely to continue to develop. Starting from criticism of sanad, matan, ma'ani and others. From various aspects of hadith criticism, each character or expert has its own tendency. Muhammad al-Gazali, for example, is known as a person who focuses on matan criticism. Nusantara Hadith figure, Syuhudi Isma'il is known for his Ma'anil Hadith knowledge. On the other hand, a modern figure, Nasir al-Din al-Albani is known as a very productive person in producing works in the field of hadith. He is known as a person who is very focused on sanad criticism. In the context of science, the expertise of a character cannot be separated from sharp criticism. The criticism that gives rise to dialectic, so that science progresses. Through this article, the author tries to understand and analyze al-Albani's thoughts. Specifically in the book entitled al-Ajwibah al-Nafi'ah 'an Mas'alah Masjid al-Jami'ah. In this work, the author concludes that there is an inconsistency in al-Albani's thinking because it is often contradictory. Therefore, the author will describe the inconsistency of these thoughts.